Quelle traduction des stratégies territoriales de transition énergétiques dans les choix opérationnels des projets d’aménagement ? L’exemple de Bordeaux Saint-Jean Belcier - Guilhem Blanchard (Développement Durable et Territoires)
Even though territorial energy plans are becoming essential within energy transition policies, their linkage with performing devices such as land development projects is still poorly understood. This article analyzes the dynamics of translation between territorial strategies and energy-related choices operated in urban development projects. Focusing on the trajectory of heating-supply choices in one urban development project in Bordeaux (France), we highlight the various roles played by the energy strategy within the project activity, and reveal how local planners proceed with translation work in order to integrate strategic directions into processes that are mainly driven by operational concerns.